Hoạt động của đới đứt gãy Sông Hồng trong Pliocen - Đệ Tứ - Vũ, Phạm Năng; Hưng, Doãn Thế; Hương, Phan Thiên (Vietnam Journal of Earth Sciences, 2018)
The tectonic activity of the Red River fault zone in pliocene - euaternary